Testing of Two-Phase Cooling of Bipolar Plates for Fuel Cells - Gerner, H.J. van; Mühlthaler, G.; Buntz, M.B. (My University, 2025)
Hydrogen-powered fuel cells are the preferred energy source for electric aircraft. However, for aircraft applications, it is of upmost importance to reduce the mass of the fuel cell system. A considerable amount of the total system mass is due to the fuel cell cooling system. This paper discusses two-phase cooling of the bipolar plates in a fuel cell stack. A twostep approach was used. First, test were carried out with machined plates with a geometry similar to bipolar plates. In a second step, actual bipolar plates were tested, including the membranes, seals and gaskets that are present in a fuel cell. These bipolar plates are from a standard fuel cell stack and are intended for water/glycol cooling. The tests show that these standard bipolar plates can be used with two-phase cooling with methanol